2000
DOI: 10.1001/archsurg.135.10.1168
|View full text |Cite
|
Sign up to set email alerts
|

Interval Nodes

Abstract: Background: Any sentinel lymph node that receives lymph drainage directly from a primary melanoma site, regardless of its location, may contain metastatic disease. This is true even if the sentinel node does not lie in a recognized node field. Interval (in-transit) nodes that lie along the course of a lymphatic vessel between a primary melanoma site and a recognized node field are sometimes seen during lymphatic mapping for sentinel node biopsy. If drainage to such interval nodes is ignored by the surgeon duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(13 citation statements)
references
References 17 publications
0
13
0
Order By: Relevance
“…In some cases, it is difficult to determine if lymphatic channels flow into lymph nodes or just overlap lymph nodes. However, clinical recurrence might also occur in interval nodes that are sentinel lymph nodes if they are not subjected to biopsy during initial surgical treatment, and interval nodes not be overlooked if the sentinel lymph node biopsy procedure is to be as accurate as possible in all patients (Uren et al 2000). Therefore, careful observation with repetition and adjustment of window level and width is enormously needed.

Diagnostic confidence values of sentinel lymph node assessment of the lower extremities

…”
Section: Discussionmentioning
confidence: 99%
“…In some cases, it is difficult to determine if lymphatic channels flow into lymph nodes or just overlap lymph nodes. However, clinical recurrence might also occur in interval nodes that are sentinel lymph nodes if they are not subjected to biopsy during initial surgical treatment, and interval nodes not be overlooked if the sentinel lymph node biopsy procedure is to be as accurate as possible in all patients (Uren et al 2000). Therefore, careful observation with repetition and adjustment of window level and width is enormously needed.

Diagnostic confidence values of sentinel lymph node assessment of the lower extremities

…”
Section: Discussionmentioning
confidence: 99%
“…McMasters et al, with 99m Tc sulfur colloid radioactive agent, reported 3.1% of interval nodes [4]. Uren et al reported an incidence of interval nodes of 7.2% of patients using 99m Tc-labelled antimony trisulfide colloid that is a very small radioactive particle [3]. Roozendaal et al, like in our institution, used 99m Tc-labelled human albumin colloid, with an identification rate of interval nodes of 5.8% [9].…”
Section: Clinical Implication and Surgical Managementmentioning
confidence: 99%
“…Although most melanomas drain to the predicted classical anatomical basins (cervical, axillary, and inguinal nodes), some patients drain to lymph nodes in unpredicted sites, so-called interval nodes, aberrant nodes, intercalated, or unexpected nodes. These ā€œnot classicalā€ sentinel nodes are those lymph nodes lying along the course of a lymphatic collecting vessel between the primary tumor site and the draining basin or that lymph nodes located in a nodal basin outside the anatomical predicted nodal field [3]. These peculiar sentinel nodes may contain micrometastatic disease and may be the only site of nodal involvement [4].…”
Section: Introductionmentioning
confidence: 99%
“…While most melanomas show lymphatic drainage to usual nodal basins (axillary, inguinal, and cervical regions), some patients also have drainage to lymph nodes outside these regions [5, 6, 9, 12]. Lymphatic nodes in the area between the primary melanoma and the regional basins are called ā€œin-transit nodesā€, ā€œinterval nodesā€, or ā€œinterval sentinel lymph nodesā€, and by definition are also SLNs [2ā€“5, 9, 10]. …”
Section: Introductionmentioning
confidence: 99%